Radical Documentaries, Neoliberal Crisis and Post-Democracy - Eugenia Siapera; Lambrini Papadopoulou (tripleC: Communication, Capitalism & Critique)
This article examines radical documentaries in Greece as a response to neoliberal crisis and post democracy. In a context where mainstream media have made themselves irrelevant, facing historical lows in trust and credibility, we found that radical documentaries have emerged outside the commodification of information and form part of the growing social or solidarity economy in Greece. Our analysis shows that these documentaries operate through a different political economy, that involves collaborative practices and that they are firmly oriented towards society rather than the political sphere. Overall, we found that radical documentaries are seeking to recuperate the media through engaging professional media workers, journalists, film directors, academics and actors; they operate through reclaiming media know-how; through radicalizing the financing, production and distribution by refusing to participate in commodification processes; and through recreating commonalities by thematizing the common, the public, and responsibility towards others.Their specific political role is found to be one of helping to restore the social body and to contribute to processes of commoning, whereby solidarity and social trust is recovered.